2015
DOI: 10.1038/nn.4198
|View full text |Cite
|
Sign up to set email alerts
|

Modular composition and dynamics of native GABAB receptors identified by high-resolution proteomics

Abstract: GABAB receptors, the most abundant inhibitory G protein-coupled receptors in the mammalian brain, display pronounced diversity in functional properties, cellular signaling and subcellular distribution. We used high-resolution functional proteomics to identify the building blocks of these receptors in the rodent brain. Our analyses revealed that native GABAB receptors are macromolecular complexes with defined architecture, but marked diversity in subunit composition: the receptor core is assembled from GABAB1a/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
154
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(188 citation statements)
references
References 48 publications
4
154
0
Order By: Relevance
“…The KCTD subunits influence activation/deactivation kinetics and desensitization of the receptor response (Fritzius et al, 2017;Turecek et al, 2014). Moreover, KCTD16 was shown to scaffold effector Ca 2þ and hyperpolarization-activated cyclic nucleotide gated (HCN) channels at the receptor (Schwenk et al, 2016). Knock-out mice demonstrated that KCTD12 and KCTD16 modulate the postsynaptic GABA B receptor response and alter the duration of sIPSCs (Booker et al, 2017;Fritzius et al, 2017;Schwenk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The KCTD subunits influence activation/deactivation kinetics and desensitization of the receptor response (Fritzius et al, 2017;Turecek et al, 2014). Moreover, KCTD16 was shown to scaffold effector Ca 2þ and hyperpolarization-activated cyclic nucleotide gated (HCN) channels at the receptor (Schwenk et al, 2016). Knock-out mice demonstrated that KCTD12 and KCTD16 modulate the postsynaptic GABA B receptor response and alter the duration of sIPSCs (Booker et al, 2017;Fritzius et al, 2017;Schwenk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is well placed to influence GABA B modulation of neuronal excitability, oscillatory network activity, and cognitive functions such as learning and memory [42][43][44][45]. The different behavioural phenotypes that can be attributed to KCTD16 (present study) and KCTD12 [39] coincide with their distinct domain structures and to their being constituents of distinct receptor complexes [41,57]. As a group and individually, therefore, evidence is emerging that auxillary KCTD subunits of GABA B receptors are of regulatory relevance to specific learning and memory processes that are important in adaptive behaviour and that also underlie important psychopathologies in neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 49%
“…The auxillary subunit KCTD16, which as noted above is highly expressed in a number of brain regions including amygdala and hippocampus [40], regulates the GABA B receptors with respect to their gating of postsynaptic ion channels, such as hyperpolarization-activated cyclic nucleotide gated (HCN) channels [6,41]. As such, it is well placed to influence GABA B modulation of neuronal excitability, oscillatory network activity, and cognitive functions such as learning and memory [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible mechanisms may involve NMDA receptor, which often participates in long-lasting plastic changes and has been shown to control trafficking and surface expression of GABAbR via the CaMKII-AMPK phosphorylation cascade (Guetg et al, 2010;Maier et al, 2010;Terunuma et al, 2010). Changing GABAbR kinetics properties by the KCTD family of axillary proteins (Gassmann and Bettler, 2012;Schwenk et al, 2010) or modulation via several recently discovered interacting proteins (Schwenk et al, 2016) may also be involved. Some of these mechanisms have been documented in dendrites of glutamatergic neurons but remain to be tested in GABAergic terminals.…”
Section: Gababr-dependent Alterations In Pv-in and Som-in Inputs To Lmentioning
confidence: 99%